Pea3 determines the isthmus region at the downstream of Fgf8‐Ras‐ERK signaling pathway. (22nd December 2015) - Harada, Hidekiyo; Omi, Minoru; Sato, Tatsuya; Nakamura, Harukazu
Abstract : It has been shown that strong Fgf8 signal activates Ras‐ERK signaling pathway to determine metencephalon, which consists of rhombomere 1 (r1), where the cerebellum differentiates, and isthmus (r0). The present study was undertaken to check if Ets type transcription factor Pea3 functions downstream of Ras‐ERK signaling to determine metencephalon. Pea3 misexpression resulted in repression of Otx2 expression in the mesencephalon, induction of Gbx2 and Fgf8 expression in the mesencephalon, and differentiation of the trochlear neurons in the posterior mesencephalon. Fate change of the tectum to the cerebellum did not occur. Repression of Pea3 function by misexpressing the chimeric molecule of Engrailed repressor domain EH1 and Pea3 (eh1‐Pea3) resulted in induction of Otx2 expression in the metencephalon, repression of Gbx2 and Fgf8 expression in the metencephalon, and differentiation of the oculomotor neurons in the isthmus. It was concluded that Pea3 plays a pivotal role in determination of the isthmus (r0) property downstream of Fgf8‐Ras‐ERK signaling. Abstract : Pea3 expression was localized in the isthmus among the presumptive FGF8/Ras‐ERK signaling target Ets‐Pea3 subfamily members. Pea3 misexpression resulted in isthmus enlargement. Our data indicated that Pea3 may be a key transcription factor that determines isthmus fate at the downstream of FGF8/Ras‐ERK signaling pathway.